THE IMPACT OF ELECTRONIC MARKETING ON ECONOMIC DEVELOPMENT - A THEORETICAL APPROACH - Hanaa NAJM; Mustafa AL-MAFRACHI; Luiza PASCAL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The concept of marketing is broad, with a large number of studies conducted on this topic. These studies discuss various marketing tools as well as strategies for directing the business towards success. Today, internet marketing has gained more budgets for marketing efforts, and given its importance in developing the economy, it is imperative to use modern methods for its development. The aim of the research is to study the impact of electronic marketing on developing the economies of countries by studying a comparison between traditional marketing and electronic marketing. The research used the study of economic factors involved in marketing such as cost, speed, and market ... etc. and compared them in both electronic and traditional marketing. The research concluded that there is a positive effect on the use of electronic marketing and the development of the economy. The research found clear differences in adopting electronic marketing to raise the marketing efficiency of all commodities and develop an economy.